ANALISIS KEMAUAN DAN KEMAMPUAN MEMBAYAR SERTA PREDIKSI POLA PERJALANAN KONSUMEN RUTE PASAR KOTA KARANG – PASAR LEMPASING BANDAR LAMPUNG - Aditya Mahatidanar Hidayat; Prasetya Wibisono (Jurnal Teknik Sipil, 2017)
The  development  of  livelihood  activities  in  Bandar  Lampung  City  precisely  in  the  area  of  Jalan Laksamana R.E.Martadinata has been very rapid which will also generate an increase in traffic flow, so that efforts are needed to improve transportation services. This study aims to determine the rates given by the  Pasar  Kota  Karang  -  Lempasing  Market  Bandar  Lampung  route,  reviewing  whether  the  socio- economic  characteristics  or  attributes  of  transportation  services  are  the  most  dominant,  the  ability  of consumers to pay and know the  pattern of travel. The research was conducted by means of  a survey to find  out  the  travel  pattern  and  the  willingness  and  ability  of  consumers  to  determine  transportation service  tariffs  with  the  service  attributes  provided.  The  survey  object  is  the  community  around  Jalan Laksamana R.E.Martadinata, starting from the intersection of Jalan Ikan Sebelah to the TPI Lempasing. The data obtained are then processed with the SPSS v.24 software program. The tariff that is most given by  consumers  to  the  Bus  Rapid  Trans  service  plan  with  Pasar  Kota  Karang  route  -  Bandar  Lampung Lempasing Market based on the willingness to pay is Rp.2000,- . Based on the ability to pay by looking at the results of the regression model obtained, it is obtained information about the number of coefficients of socio-economic  factors  with  variables  of  gender,  age,  income,  education,  intensity  of  use  of  BRT, residence, transportation costs, mode of transportation, and destination of Rp. 3.231,- . For the number of coefficients of service attribute factors which consist of student tariffs, operating hours, availability of bus  stops  and  availability  of  goods,  there  are  no  significant  results  that  affect  the  tariff  determination. The  most  popular  travel  origins  are  number  1  with  locations  in  the  coral  city  market  and  the  most popular travel destinations, number 7 with locations on the marketplace.